Improvement of Science Learning Results With Power Point Media Through Zoom Application In Class V SD IT Annida Sokaraja - Kohwati, Septi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to describe that student learning outcomes in science learning increased with Power Point media through the zoom application in class V SDIT Annida Sokaraja. The method used in this research is Classroom Action Research which consists of planning, implementing, observing and reflecting stages, which are carried out in 2 cycles. The subjects in this study were 18 students of grade V SDIT Annida Sokaraja. Data collection techniques using observation techniques and giving evaluation questions. Data analysis techniques were carried out to analyze the results of observations on teacher activities and student evaluation results assessment sheets to determine the increase in learning outcomes. In learning activities, teacher activities have increased from cycle I and cycle II. In the first cycle the teacher's activity reached 93% and in the second cycle the teacher's activity reached 98%. While student learning outcomes in cycle I reached 86% and cycle II student activity reached 94%. From these results it can be concluded that the use of power point media through the zoom application can improve the learning outcomes of fifth grade students of SDIT Annida Sokaraja. The obstacle experienced in cycle I is that students are still doing other activities outside of learning with the zoom application in progress. This problem was corrected in cycle II. From the results of the study it was concluded that the fifth grade SDIT Annida Sokaraja students experienced an increase in science learning outcomes after using Power Point media with the zoom application.